Effect of S/G ratio on kraft pulping and ECF bleaching of some poplars and eucalyptus - Ventorim, Gustavo [UNESP]; Alves, Ericka F.; Penna, Lais S.; Francis, Raymond C. (My University, 2014)
The effect of syringyl:guaiacyl (S/G) ratio on kraft pulping and kraft pulping followed by O2 delignification was investigated with six poplars grown on the same site. The results showed an improvement in the ease of delignification (EOD) when the S/G ratio was increased from a low to a moderately high value. However, above that moderately high value there was no further improvement in EOD with increasing S/G ratio. Kraft pulping followed by elemental chlorine-free (ECF) bleaching was then investigated with three Brazilian eucalypti with S/G ratio of 2.69, 2.46 and 2.41. The chips with S/G = 2.69 had superior EOD compared to the chips with S/G = 2.41. However, pulps from the S/G = 2.69 chips also contained less lignin-carbohydrate complexes (LCC) than corresponding pulps from the chips with S/G = 2.41. LCC are known to retard delignification in both alkaline pulping and ECF bleaching. The S/G ratio of eucalyptus pulp lignins was estimated by nitrobenzene oxidation (NBO) of the pulps and 1H NMR or their isolated lignins. The S/G ratio decreased from a value of ≥2.46 for the lignin in two eucalyptus chip samples to <1.21 for the lignin in their kraft pulps. In general, S units appear to solubilize at a much higher rate than G units during kraft pulping.
Keywords: ECF bleaching; Hardwood; Kraft pulping; Lignin-carbohydrate complexes; S/G ratio